Smooth muscle cell CYB5R3 preserves cardiac and vascular function under chronic hypoxic stress. (January 2022) - Durgin, Brittany G.; Wood, Katherine C.; Hahn, Scott A.; McMahon, Brenda; Baust, Jeffrey J.; Straub, Adam C.
Abstract: Chronic hypoxia is a major driver of cardiovascular complications, including heart failure. The nitric oxide (NO) – soluble guanylyl cyclase (sGC) – cyclic guanosine monophosphate (cGMP) pathway is integral to vascular tone maintenance. Specifically, NO binds its receptor sGC within vascular smooth muscle cells (SMC) in its reduced heme (Fe 2+ ) form to increase intracellular cGMP production, activate protein kinase G (PKG) signaling, and induce vessel relaxation. Under chronic hypoxia, oxidative stress drives oxidation of sGC heme (Fe 2+ →Fe 3+ ), rendering it NO-insensitive. We previously showed that cytochrome b5 reductase 3 (CYB5R3) in SMC is a sGC reductase important for maintaining NO-dependent vasodilation and conferring resilience to systemic hypertension and sickle cell disease-associated pulmonary hypertension. To test whether CYB5R3 may be protective in the context of chronic hypoxia, we subjected SMC-specific CYB5R3 knockout mice (SMC CYB5R3 KO) to 3 weeks hypoxia and assessed vascular and cardiac function using echocardiography, pressure volume loops and wire myography. Hypoxic stress caused 1) biventricular hypertrophy in both WT and SMC CYB5R3 KO, but to a larger degree in KO mice, 2) blunted vasodilation to NO-dependent activation of sGC in coronary and pulmonary arteries of KO mice, and 3) decreased, albeit still normal, cardiac function in KO mice. Overall, these data indicate that SMC CYB5R3 deficiency potentiates bilateral ventricular hypertrophy and blunts NO-dependent vasodilation under chronic hypoxia conditions. This implicates that SMC CYB5R3 KO mice post 3-week hypoxia have early stages of cardiac remodeling and functional changes that could foretell significantly impaired cardiac function with longer exposure to hypoxia. Graphical abstract: Unlabelled Image Highlights: Chronic hypoxia is an underlying cause of pulmonary hypertension and heart failure. In chronic hypoxia, smooth muscle specific deletion of CYB5R3 increases cardiac hypertrophy. Smooth muscle cell CYB5R3 is important for maintaining NO-dependent vasodilation under chronic hypoxic stress.